2018
DOI: 10.14221/ajte.2018v43n6.4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the School-Work Environment on Mathematics Teachers’ Motivation for Teaching: A Self-Determination Theoretical Perspective

Abstract: Guided by self-determination theory, this study investigated the extent to which factors of teachers' school-work environments predict their self-efficacy and intrinsic value for teaching. Participants were 217 mathematics teachers working in Texas public schools. Results indicated that principals' autonomy support positively predicted teachers' self-efficacy and intrinsic value for teaching beyond years of teaching experience, mathematics background, and grade level taught. Moreover, the negative effects of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
(81 reference statements)
0
5
0
2
Order By: Relevance
“…This is unfortunate as group work contributes with positive cognitive effects and can prevent social deprivation, which is a risk factor during quarantine and social distancing requirements (cf. Corkin et al, 2018).…”
Section: Challeng E Sandopp Ortunitie Sforremotele Arningmentioning
confidence: 99%
“…This is unfortunate as group work contributes with positive cognitive effects and can prevent social deprivation, which is a risk factor during quarantine and social distancing requirements (cf. Corkin et al, 2018).…”
Section: Challeng E Sandopp Ortunitie Sforremotele Arningmentioning
confidence: 99%
“…Another barrier to ERL frequently mentioned by students was social-deprivation [ 15 ]. Despite the technical possibilities provided by the applications they use, teachers did not offer their students tasks and group work that required cooperation [ 16 ], whilst normally, such active and engaging learning activities appeared to be more effective than learning individually with the use of materials prepared by teachers [ 15 ]. Remote learning undoubtedly presents challenges for students with SEN. Research conducted in the USA by Averett [ 17 ] among families of students with disabilities indicated that most of them struggled with two types of difficulties: (1) the children’s specific needs while learning at home were different from those at school (new, previously unknown problems emerged), and (2) schools did not provide comprehensive distance support.…”
Section: Introductionmentioning
confidence: 99%
“…Selain faktor motivasi guru dan kepemimpinan kepala sekolah, faktor lain yang mempengaruhi kinerja guru adalah lingkungan kerja (Xu, Z., Özek & Hansen, 2015). Lingkungan kerja merupakan salah satu faktor yang mempengaruhi kinerja guru (Corkin et al, 2018). Jika guru merasakan suasana kerja yang kondusif di sekolahnya, diharapkan kinerja guru akan meningkat dan mencapai prestasi akademik yang memuaskan.…”
Section: Pendahuluanunclassified